STUDI LITERATUR : PEMBELAJARAN PERKALIAN DAN PEMBAGIAN DI KELAS RENDAH - Nurhaswinda; Chintya Alpita Yani; Arini Fajpadela; Nurul Sabila; Salsa Billa (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to examine the teaching of multiplication and division in lower elementary grades. The study employs a qualitative approach using a literature review method through descriptive analysis of 10 relevant scientific journals published between 2021 and 2026. The results indicate that multiplication and division instruction in elementary school lower grades should prioritize strengthening conceptual understanding over mere procedural mastery. Students’ learning difficulties are generally attributed to instruction that remains rote-memorization-oriented and fails to provide concrete, contextual learning experiences that help students grasp the meaning of repeated addition and the concept of division as a process of sharing equally. Various findings indicate that the implementation of innovative learning models, the use of manipulative and digital media, as well as problem-based and real-world context-based learning approaches can significantly improve conceptual understanding, active engagement, and student learning outcomes. Therefore, the teaching of multiplication and division in lower grades needs to be designed systematically, meaningfully, and student-centered to build a strong foundation in numeracy as the basis for mathematics learning at subsequent levels.